The type II RAF inhibitor tovorafenib in relapsed/refractory pediatric low-grade glioma: the phase 2 FIREFLY-1 trial - Kilburn, Lindsay B.; Khuong-Quang, Dong-Anh; Hansford, Jordan R.; Landi, Daniel; van der Lugt, Jasper; Leary, Sarah E. S.; Driever, Pablo Hernáiz; Bailey, Simon; Perreault, Sébastien; McCowage, Geoffrey; Waanders, Angela J.; Ziegler, David S.; et al. (Nature medicine, 2024)
BRAF genomic alterations are the most common oncogenic drivers in pediatric low-grade glioma (pLGG). Arm 1 (n = 77) of the ongoing phase 2 FIREFLY-1 (PNOC026) trial investigated the efficacy of the oral, selective, central nervous system-penetrant, type II RAF inhibitor tovorafenib (420 mg m−2 once weekly; 600 mg maximum) in patients with BRAF-altered, relapsed/refractory pLGG. Arm 2 (n = 60) is an extension cohort, which provided treatment access for patients with RAF-altered pLGG after arm 1 closure. Based on independent review, according to Response Assessment in Neuro-Oncology High-Grade Glioma (RANO-HGG) criteria, the overall response rate (ORR) of 67% met the arm 1 prespecified primary endpoint; median duration of response (DOR) was 16.6 months; and median time to response (TTR) was 3.0 months (secondary endpoints). Other select arm 1 secondary endpoints included ORR, DOR and TTR as assessed by Response Assessment in Pediatric Neuro-Oncology Low-Grade Glioma (RAPNO) criteria and safety (assessed in all treated patients and the primary endpoint for arm 2, n = 137). The ORR according to RAPNO criteria (including minor responses) was 51%; median DOR was 13.8 months; and median TTR was 5.3 months. The most common treatment-related adverse events (TRAEs) were hair color changes (76%), elevated creatine phosphokinase (56%) and anemia (49%). Grade ≥3 TRAEs occurred in 42% of patients. Nine (7%) patients had TRAEs leading to discontinuation of tovorafenib. These data indicate that tovorafenib could be an effective therapy for BRAF-altered, relapsed/refractory pLGG. ClinicalTrials.gov registration: NCT04775485.